Healthy aging based on the strengthening of cognitive abilities and the reinforcement of healthy practices of a group of older adults - Arias Jiménez, María Stephanie (2020)
Objective: to strengthen the cognitive capacities oriented to a healthy aging from the Health Promotion focus in a group of elderly people ascribed to the Clínica Integrada de Tibás, 2018. Methodology: mixed approach, preexperimental desing based on a test/post test with a single group. The study population were the elderly people ascribed to the Clinica Integrada de Tibás, the target population: 24, all volunteers. Results: in the diagnosis phase, the application of the MoCA shows that the lower scores are those indicated in other studies as the most affected cognitive capacities in the older adults. In addition, the Indice de KATZ  showed that the majority of the group does not have any disabilities. Regarding the subject of perceptions about the aging process, it was observed that 80% of the participants possesses knowledge similar to the one contemplated for this study, and 90% identifies the myths and stereotypes of the aging process. Conclusions: The strategies and techniques implemented in the learning process allowed the population to appropriate each of the topics, reinforce certain cognitive capacities and adopt healthy practices, which can be seen in the changes reflected in the ex post evaluations, since they show an increase in the MoCA results and greater amplitude of knowledge. Finally, this study reinforces that the topic of healthy practices and cognitive capacities can be promoted from the lines of health promotion: creation of healthy environments and development of personal skills and attitudes.